Descriptive peer drinking norms and binge drinking: Enhancement motives as a mediator and alcohol resistance self-efficacy as a moderator - Chen, Jianyong; Li, Yuzhi; Zhang, Yaping; Feng, Ju; Jia, Liang (Frontiers in Psychology, 2022)
The association between descriptive norms regarding peer drinking and college students’ binge drinking has been established; however, the mediating and moderating mechanisms underlying this relationship among first- and second-year college students remain minimally explored. Drawing on social norms theory, motivational model of alcohol use, and the theory of normative social behavior, the current study investigated whether enhancement drinking motives mediated the relationship between descriptive norms regarding peer drinking and college students’ binge drinking, and whether this relationship was moderated by drinking refusal self-efficacy. Five hundred and nineteen first- and second-year college students (Mage = 19.19 years, SD = 0.98) who were from four universities and had at least one time of heavy episodic drinking during the last year completed self-report questionnaires. After controlling for sex, age, and university variable, stronger descriptive norms regarding peer drinking were positively associated with a greater frequency of binge drinking. Enhancement drinking motives partially mediated the effects of descriptive peer drinking norms on binge drinking. Furthermore, drinking refusal self-efficacy moderated the direct effects of descriptive peer drinking norms on binge drinking. Compared with college students who reported high drinking refusal self-efficacy, the direct effects of descriptive peer drinking norms on binge drinking were stronger among students with low drinking refusal self-efficacy. These findings point to the potential value of alcohol intervention approaches including efforts to help first- and second-year college students change enhancement drinking motives and increase ability of resisting drinks in the context of pervasive peer drinking.